Constant current induction brazing process optimization of AgCdO15-Cu electrical contact. (March 2020) - Zhou, Lei; Zhu, Shiliang; Zheng, Wenjia; Li, Tianjian; Wu, Laijun; Zhang, Zhongdian; Lei, Zhenglong
Abstract: The current waveform of the heating phase, the holding current and holding time of the holding phase were optimized in this study to solve the problems of low brazing ratio and poor quality stability of constant current induction brazing. Pulse current was used to replace constant current in the heating phase to improve the uniformity of the radial temperature distribution of electrical contact. The simulation results showed that the uniformity of the radial temperature field of pulse current heating is better than constant current heating. The experiment was conducted with constant and pulse induction brazing separately. Compared with constant current induction brazing, pulsed current induction brazing has a higher brazing ratio and a wider process window for brazing time. The maximum brazing ratio of constant induction brazing is 87.62 %, and pulse induction brazing is 96.61 %. Besides, the shear strength of brazing joint can be improved by extending hold time. Different from the effect of holding time, the shear strength increases first and then decreases with the increase of holding current, and it should be selected according to the actual situation.